Glossophobia: The Hidden Barrier to Student Success - Retno Wulandari (Asosiasi Asesmen Pendidikan (AAP), 2024)
This research aims to determine the influence of glossophobia on the learning outcomes of Class X students at SMA Negeri 104 Jakarta. The research method used is quantitative. The sample used was 150 class X students of SMA Negeri 104 Jakarta. The statistical hypothesis used is simple linear regression analysis using the SPSS 27 program. The sampling technique used in this research is random sampling technique. The instrument used was a glossophobia questionnaire with a total of 33 items. Meanwhile, the learning outcome variable uses Odd Semester UAS report scores. The analysis technique used is simple linear regression analysis. The research results show that there is an influence of glossophobia (X) on learning outcomes (Y). The influence obtained is 0.038, while the significance value is 0.025 <0.05, meaning Ha is accepted that there is a significant influence between glossophobia and learning outcomes.